SWOT-Based Governance Assessment of BP Batam: Addressing Institutional, Regulatory, and Investment Barriers - Yudithia, Yudithia; Yuniartoto, Wahyo; Suryahadi, Suryahadi; Soares, Augusto; Dewi, Luh Komang Candra (Austronesia Akademika, 2025)
As Indonesia intensifies its commitment to evidence-based governance and performance accountability through frameworks like SAKIP, there is growing urgency to evaluate the effectiveness of key institutions such as BP Batam. Positioned as the governing body for a strategic Free Trade Zone, BP Batam is tasked with managing licensing, investment, and asset optimization amidst complex regulatory and environmental challenges. This study investigates BP Batam’s governance performance in 2024, which, despite notable successes in investment realization and public satisfaction, calls for a deeper strategic analysis to assess the sustainability and inclusivity of these outcomes. The purpose of this research is to assess institutional strengths, weaknesses, opportunities, and threats using a SWOT framework in order to provide actionable recommendations for policy refinement and governance enhancement. Employing a qualitative descriptive design, the study analyzes secondary data, including the 2024 LAKIP report and related policy documents, selected through purposive sampling. Data were interpreted using thematic content analysis and SWOT matrix coding. The findings indicate that while BP Batam has surpassed its economic targets, it faces internal challenges such as uneven service quality, limited digital integration, and low stakeholder participation. Externally, overlapping jurisdiction and ecological vulnerabilities pose strategic risks. The conclusion emphasizes the need for digital governance acceleration, stakeholder-centered engagement, and regulatory synchronization to transform BP Batam into a model of inclusive and resilient governance.